The Effect of a Counseling Program in Lowering Self-automatic Judgment for Educational Counselors - فضيل عبد الله, مالك (Journal of College of Education, 2021)
The current research aims to:1- Learn about automatic self-judgment by educational counselors.2- Building an indicative program to reduce automatic self-judgment for educational counselors.3- Knowing the effect of the extension program, automatic self-judgment of educational counselors.To achieve the third goal, the researcher formulated the following null hypothesis: There are no statistically significant differences between the average grades of the experimental group and the control group on the scale of automatic judgments for the self in the post-test, and the current research has been determined by educational counselors working in the general directorates of education in Wasit and Dhi Qar governorate in schools Intermediate, secondary and middle school studies for the morning study for the academic year (2019-2020). The current research community consisted of (917) male and female guides, and the statistical analysis sample reached (250) male and female guides, and the Darraji scale (2015) was adopted for automatic judgments for the self after presenting it to a group of arbitrators. In the field of education and psychology, the psychometric characteristics of validity and consistency of the scale were extracted, and the indicative program was built according to Albert Else's theory, The counseling program consisted of (12) sessions, and the content of the counseling program sessions was presented to a group of arbitrators and specialists in psychological counseling, and members of the two groups (experimental and control) were rewarded in the variables (age, length of service, and the degrees of the sample members on the scale of automatic judgments for the self in the pre-test. The sample of the counseling program reached (10) members of the counselors in the control group and the same in the experimental group, and the researcher used the appropriate statistical means and with the help of the statistical program (SPSS) in analyzing the research data, and the results of the research showed that the educational counselors have automatic judgments for the self. The results show that there is a statistically significant difference, and in favor of the experimental group the post-test, and in favor of the indicative program, In light of the results, the researcher reached a set of conclusions, recommendations and suggestions.